Eco-efficiency to support selection of energy conservation measures for buildings: A life-cycle approach. (1st December 2022) - Tadeu, Sérgio; Rodrigues, Carla; Marques, Pedro; Freire, Fausto
Abstract: Energy efficiency of buildings is expected to improve by 2050, according to recent energy efficiency legislation and decarbonization plans. However, the methodology framework currently adopted in energy efficiency programs to assess the energy, environmental, and cost performance of buildings has several limitations. The main goal of this article is to propose an eco-efficiency approach integrating life-cycle assessment (LCA) and cost optimality to support the decision-making of energy conservation measures (ECMs) and the development of effective incentives to improve the performance of buildings. This approach contributes to methodological advances in the assessment of ECMs in buildings, considering more accurate energy needs and conversion factors, and robust indicators, adopting a life-cycle perspective. It is applied to the retrofitting of a reference building, assessing alternative ECMs for the replacement of existing energy systems with low efficiency. Results show that ECMs reduce significantly life-cycle impacts, particularly the gas boiler for the current electricity mix scenario and the heat pump for the decarbonization scenario. This article demonstrated how a comprehensive eco-efficiency assessment of ECMs, adopting LCA-based indicators combined with a decarbonization strategy, could support the design of incentives for future policies, that would effectively reduce the environmental burden of the building stock in a cost-effective way. Highlights: Limitations in currently adopted methodologies can lead to misguided policies. Decision support approach for policymakers, experts and building owners. LCA-based indicators showed to be more effective than single primary energy needs. More accurate and updated CO2 emission and energy conversion factors are shown. Incentives to replace building systems must be in line with decarbonization strategies.